2011
DOI: 10.1016/j.cep.2011.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of fouling resistances under dynamic membrane filtration

Abstract: The mechanisms of fouling in the ultrafiltration of polyethylene glycol (PEG) are analyzed using the complete blocking and the intermediate blocking Hermia´s models adapted to crossflow filtration. 1 The parameters of these models were theoretically

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…4A, where it can be observed that the membrane fouling resistance, R f , increases with P TM for a constant v t . Similar results were reported by Choi et al and Vincent-Vela et al [39,46]. These results are supported by the concentration polarization and fouling resistances and the normalized values calculated and reported in Table 5, in particular the normalized fouling build-up rate values D(R f /R m )/Dt (min À1 ) which provide more precise information about the dynamic fouling build-up during the RO operation time under the different operating conditions assayed.…”
Section: Analysis Of the Concentration Polarization And Fouling Resissupporting
confidence: 92%
“…4A, where it can be observed that the membrane fouling resistance, R f , increases with P TM for a constant v t . Similar results were reported by Choi et al and Vincent-Vela et al [39,46]. These results are supported by the concentration polarization and fouling resistances and the normalized values calculated and reported in Table 5, in particular the normalized fouling build-up rate values D(R f /R m )/Dt (min À1 ) which provide more precise information about the dynamic fouling build-up during the RO operation time under the different operating conditions assayed.…”
Section: Analysis Of the Concentration Polarization And Fouling Resissupporting
confidence: 92%
“…However, a major operating problem for membrane ltration is concentration polarization, resulting in the buildup of solutes on the membrane surface, thereby reducing the separation efficiency. [23][24][25][26] In electro-ultraltration, the power of ltration is derived from an electric eld, which drives charged molecules to move through the solution. Moreover, the driving speed and directions differ for different molecules, depending on their charges, sizes, and masses.…”
Section: Resultsmentioning
confidence: 99%
“…The striking difference in the permeability coefficients between pure water and OMWST-2 (36.2%– 39.0% for N Re = 1.3 × 10 4 − 2.6 × 10 4 ) shall be attributed to concentration polarization and fouling resistance taking place on the boundary region of the RO membrane (Table 4) [25,26]. A guided focus on Table 4 permits us to note that reduction of the concentration polarization ( R CP ) on the RO membrane equal to 26.3% was provided upon an increment of the turbulence on the membrane to values of N Re = 2.6 × 10 4 .…”
Section: Resultsmentioning
confidence: 99%
“…Results withdrawn show a value of the pure water permeability coefficient ( K w ) of 1.41 L h −1 m −2 bar −1 , whereas K measured with the secondary-treated effluent (OMWST-2) was equal to 0.86 L h −1 m −2 bar −1 upon turbulent regime over the membrane (tangential velocity equal to v t = 2.55 m s −1 , corresponding to Reynolds number N Re = 1.3 × 10 4 ). The striking difference in the permeability coefficients between pure water and OMWST-2 (36.2%– 39.0% for N Re = 1.3 × 10 4 − 2.6 × 10 4 ) shall be attributed to concentration polarization and fouling resistance taking place on the boundary region of the RO membrane ( Table 4 ) [ 25 , 26 ]. A guided focus on Table 4 permits us to note that reduction of the concentration polarization ( R CP ) on the RO membrane equal to 26.3% was provided upon an increment of the turbulence on the membrane to values of N Re = 2.6 × 10 4 .…”
Section: Resultsmentioning
confidence: 99%